Workshop Cultures of the Andijan Region of the XIX-XX Centuries - Ruziev Nuriddin Mukhamadalievich (International Journal on Integrated Education, 2021)
The article provides information about the master potters who worked in the Andijan region in the 19th-20th centuries. The features of the Andijan school in pottery schools, the technology of Andijan ceramics in the decoration of ceramics are discussed.